The increased level of β1,4-galactosyltransferase required for lactose biosynthesis is achieved in part by translational control - Charron, Martin (The National Academy of Sciences, 1998)
β1,4-Galactosyltransferase (β4GalT-I) participates in both glycoconjugate biosynthesis (ubiquitous activity) and lactose biosynthesis (mammary gland-specific activity). In somatic tissues, transcription of the mammalian β4GalT-I gene results in a 4.1-kb mRNA and a 3.9-kb mRNA as a consequence of initiation at two start sites separated by ≈200 bp. In the mammary gland, coincident with the increased β4GalT-I enzyme level (≈50-fold) required for lactose biosynthesis, there is a switch from the 4.1-kb start site to the preferential use of the 3.9-kb start site, which is governed by a stronger tissue-restricted promoter. The use of the 3.9-kb start site results in a β4GalT-I transcript in which the 5′- untranslated region (UTR) has been truncated from ≈175 nt to ≈28 nt. The 5′-UTR of the 4.1-kb transcript [UTR(4.1)] is predicted to contain extensive secondary structure, a feature previously shown to reduce translational efficiency of an mRNA. In contrast, the 5′-UTR of the 3.9-kb mRNA [UTR(3.9)] lacks extensive secondary structure; thus, this transcript is predicted to be more efficiently translated relative to the 4.1-kb mRNA. To test this prediction, constructs were assembled in which the respective 5′-UTRs were fused to the luciferase-coding sequence and enzyme levels were determined after translation in vitro and in vivo. The luciferase mRNA containing the truncated UTR(3.9) was translated more efficiently both in vitro (≈14-fold) and in vivo (3- to 5-fold) relative to the luciferase mRNA containing the UTR(4.1). Consequently, in addition to control at the transcriptional level, β4GalT-I enzyme levels are further augmented in the lactating mammary gland as a result of translational control.